The Effect Of Adding Snakehead Fish Meat On Acceptability And Nutritional Content In Nugget Production - Mustika, Dela; Azwar, Azwar; Dari, Dini Wulan (Sean Institute, 2024)
Fish is one of them a large source of animal protein consumed society, it's easy got it, but the price is relatively not cheap. In 100 grams of fresh fish less more contains 17% protein, 4.50% fat, 2.52 - 4.5% minerals, and 76% water. From composition the can seen that fish have High protein value and content the fat low so that Lots give benefit health for body man. By general content nutrition of fish is very good For growth, esp growth for age children. The fish protein content is sufficient big namely 20% with almost identical amino sequence The same with arrangement amino acids from human protein so that absorption the protein more maximum. objective study For​​ know​​ Effect of adding meat fish​​​ There is no doubt about the acceptability and nutritional content of making nuggets. study This use design Completely Randomized Design ( CRD ), which was carried out from January to February 2023, involving 30 authors with 4 treatments. Research purposes This is For​​ know​​ Effect of adding meat fish​​​ There is no doubt about the acceptability and nutritional content of making nuggets. Analysis​ results study using organoleptic tests and analysis chemistry or mark nutrition. The panelists' evaluation of the best formulation from the overall samples of nuggets with the addition of snakehead fish meat showed that the treatment sample (A4 = 200g of wheat flour + 100g of snakehead fish meat) had the highest average score of 3.91, categorized as